Feeling Apollo: Sensory Engagement in the Sanctuary of Apollo at Klaros - Gunderson, Jaimie (Material religion, 2021)
This article explores the interplay between body and materiality in the ancient oracular Sanctuary of Apollo at Klaros. Drawing upon sensory archaeology and classical studies, the article moves beyond the static paradigm of city-as-map in order to discover the sensory experience of an ambulant body within the sanctuary. In this way, the article suggests that a visitor’s experience in Klaros was intensely sensorial. Sensory engagement began with the evocative topography of the natural landscape; continued along the via sacra with sights, smells, and sounds; and culminated in oracular consultation in the temple. Movement through the sanctuary served as a form of “circumabulatory knowing” in which the nature of Apollo was shaped by felt encounters within the sanctuary.